Comparative Analysis of Halal Certification Mechanisms Between MUI and BPJPH According to the Perspective of Law No. 33 of 2014 Concerning Halal Product Guarantee - Mochamad Doddy Syahirul Alam; Atem Atem; Murniyati Yanur; Ernida Alfiani Fauzi; M. Syaeful Anam (Asy-Syari'ah, 2023)
Abstract. This article aims to examine the diversity of halal certification in Indonesia. It is known that 2022 Indonesia's Muslim population will be the largest in the world. In line with that, the consumption of halal products in Indonesia is relatively high; therefore, Law Number 33 of 2014 concerning Halal Product Guarantee mandates that products circulating in Indonesia are guaranteed reliability. Currently, Indonesia has a Halal Product Guarantee Agency (BPJPH), which has the task of ensuring those that enter, circulate, and are traded in Indonesia, as evidenced by the ownership of halal certification by business actors (PU) and halal labels on the products produced. This paper uses qualitative research with a literature study approach (literature review), namely conducting a descriptive analysis of secondary data. The results of this paper show a change in the management of halal certification, which was previously issued through the Indonesian Ulema Council (MUI) and is now by BPJPH. In addition, two schemes for applying for halal certification can be pursued by business actors in Indonesia, namely regular and self-declaration. Currently, halal products and the halal industry are growing not only nationally but also globally, and there are at least six halal industry sectors that are of concern halal food commodities, Islamic finance, Muslim-friendly travel (halal tourism), Modest Fashion, Media and recreation and Pharma & Cosmetic.